Control of a wind system connected to the electrical network and powering a mechanical load - TOURBI SALAHEDDINE; MEITAR AHMED; BOUTOUBAT Mohamed (Université Amar Telidji- Laghouat FACULTE : TECHNOLOGIE DEPARTEMENT : Département d’Electronique, 2023)
Exploiting renewable energy allows the production of decentralized electrical energy, which contributes to a solution for powering an isolated area with the necessary energy. The main objective of this work is to control a wind energy system based on a DC machine driven by a variable speed wind turbine which is connected to the grid and powering a mechanical load. Each component of the wind system is modelled. The DC aero generator is connected to the electrical network through two series converters (DC-DC) and (DC-AC). In fact, the control by a classic regulator (PI) of the speed of the DC generator allowed us to capture the maximum power of the wind and establish the MPPT operating mode. In the same manner, another PI controller is applied to the DC/AC converter in order to regulate the DC link voltage to a smooth value. This wind system supplies a mechanical load whose speed is controlled by using a PI controller applied to a DC/DC converter.
OPTION: Automatic and industrial computing